Effect of yoga on musculoskeletal discomfort and motor functions in professional computer users. - Telles S; Dash M; Naveen KV (Work, 2009)
The self-rated musculoskeletal discomfort, hand grip strength, tapping speed, and low back and hamstring flexibility (based on a sit and reach task) were assessed in 291 professional computer users. They were then randomized as Yoga (YG; n=146) and Wait-list control (WL; n=145) groups. Follow-up assessments for both groups were after 60 days during which the YG group practiced yoga for 60 minutes daily, for 5 days in a week. The WL group spent the same time in their usual recreational activities. At the end of 60 days, the YG group (n=62) showed a significant decrease in the frequency, intensity and degree of interference due to musculoskeletal discomfort, an increase in bilateral hand grip strength, the right hand tapping speed, and low back and hamstring flexibility (repeated measures ANOVA and post hoc analysis with Bonferroni adjustment). In contrast, the WL group (n=56) showed an increase in musculoskeletal discomfort and a decrease in left hand tapping speed. The results suggest that yoga practice is a useful addition to the routine of professional computer users.